Caracterização de cultivares de arroz (Oryza sativa L.) quanto ao estresse por alumínio e análise da expressão do gene OsFRDL1. - Colares, Denise dos Santos (2009)
Aluminum is the most abundant metal in the earth s crust. Under acidic conditions, aluminum is solublized to its ionic form, which shows toxicity to plants. Aluminum rapidly inhibits root elongation and subsequently the uptake of water and nutrients, resulting in significant reduction of crop production on acid soils. Rice is one of the most aluminum-tolerant species among economically important crops. However, the physiological mechanism responsible for the high aluminum tolerance in rice has not been elucidated. On the other hand, rice genome is a model for the Poaceae and shows high sinteny with this family of plants. In this work, 30 rice cultivars were evaluated under four aluminum concentrations in hidroponic system. The genetic variability between the rice cultivars was evaluated through multivariated analysis. According to the tolerance response observed, 10 genotypes were selected to be evaluated in relation to a dose x time of exposition experiment. Finally, the expression of the gene OsFRDL1 was quantified in two rice cultivars differing in aluminum tolerance. There was variability in relation to aluminum tolerance between the 30 rice cultivars evaluated. The most tolerant genotypes were IAC 500, BRS Liderança and BRS Curinga and the sensitive ones were BR-IRGA 410, IAS 12-9 Formosa and Arroz da Terra. The tolerant cultivars IAC 500, BRS Liderança and BRS Curinga showed high genetic similarity and are promising genotypes for crosses aiming to increase aluminum tolerance in the progenies. Cultivars responded in a different way to the dose x time of exposition to aluminum experiment. Forty-eight hours of exposition to a solution containing an aluminum concentration of 14 mg L-1 showed to be the best combination of treatments to perform the screening of tolerant and sensitive cultivars. The expression of the gene OsFRDL1 was higher in the aluminum tolerant cultivar Farroupilha than in the aluminum-sensitive cultivar BRIRGA 410.